The Effect of Recovery Technique Physical Training Combination in Improving Vo2max of Volleyball Athlete - Dian Helaprahara; Rachlai Eko Arisetiawan; Mas’odi Mas’odi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
Volleyball uses a lot of anaerobic energy which can produce a lot of lactic acid that causes fatigue. Recovery is an important factor in increasing an athlete performance. The purpose of this study was to investigate the modification of recovery techniques by combining active and passive recovery techniques combined with massage. This research was an experimental study using a pure experimental design - Randomized Control Group Pretest-Posttest. The conclusion of this study is that there is a significant influence on changes in VO2max after the presence of massage treatment in the active and passive recovery groups. Massage can be an additional recovery technique during practice or competition.